THE DYNAMIC OF OUTSOURCING REGULATION WITHIN THE NATIONAL LEGAL FRAMEWORK (THE NEED FOR RECONCEPTUALIZATION OF PROTECTION FOR TEMPORARY WORKERS) - Didik Artino Jamaludin; Abdul Rachmad Budiono; Budi Santoso (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
The dynamics of outsourcing regulation bring varied impacts, especially regarding the legal protection for outsourced workers, which has been gradually regulated through Law Number 11 of 2020 on Job Creation. However, the legal protection system for outsourced workers still presents unresolved issues, particularly the imperfect concept of TUPE (Transfer of Undertakings Protection of Employment), which is a consequence of the legal transplant concept. This study is a normative juridical research with a legislative approach. The results of this study indicate that there are several factors contributing to the incomplete implementation of the TUPE concept, namely the effects of a flexible labor market and the inconsistency of the state's role in providing legal protection. These issues become evident in the imperfect regulation of the TUPE concept.